Level up: a history of regime-building at Gatt Club - Zapatero Miguel, Pablo (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Almost from the weak inception of the General Agreement on Trade and Tariffs (GATT) in 1947, the community of trade delegates and representatives that negotiated its provisions began to carefully reinforce it, with considerable creativity. From a so-called “accidental organization”, without proper institutional structure and under provisional application for decades, old-school trade diplomats, and trade lawyers subsequently, managed to progressively devise a powerful treaty-based regime and thus a critical infrastructure for international economic interdependence. The history of the GATT and now the WTO can be better understood by exploring the changing roles granted to diplomacy and law within.